Solve for g...Date: 04/08/97 at 17:44:54 From: Amanda Subject: Solve for g... I understand -3x+5x+4 = -6 to solve for x, but I don't understand g+.04g+60 = 8796. Date: 04/09/97 at 13:04:09 From: Doctor Mike Subject: Re: Solve for g... Dear Amanda, Believe it or not, you do the same thing for both problems. I'm sure you have seen the Distributive Law, though perhaps you don't call it by name all the time. There are several versions of it. The version "(A + B)*C = A*C + B*C" is the one you need here. You can think of this as telling you how to "multiply out" (A + B)*C , or you can think of it as telling you how to "factor out a C" from A*C + B*C. That is what is needed here. Let's do a side-by-side for these 2 : Original equation : -3x + 5x + 4 = -6 g + .04g + 60 = 8796 Factor out the unknown (remember, g is 1*g): (-3+5)*x + 4 = -6 (1+.04)*g + 60 = 8796 Simplify inside parentheses : (2)*x + 4 = -6 (1.04)*g + 60 = 8796 Subtract the right number from both sides: 2*x = -10 1.04*g = 8736 Divide both sides by the coefficient of the unknown: x = -10/2 g = 8736/1.04 x = -5 g = 8400 Maybe you just got confused because there were not simple small numbers used in the second problem, or perhaps because they used "g" instead of "x". Always look for a pattern. I hope this helps. -Doctor Mike, The Math Forum Check out our web site! http://mathforum.org/dr.math/ |
Search the Dr. Math Library: |
[Privacy Policy] [Terms of Use]
Ask Dr. Math^{TM}
© 1994- The Math Forum at NCTM. All rights reserved.
http://mathforum.org/dr.math/